KEDUDUKAN HUKUM ADAT DALAM SISTEM KETATANEGARAAN INDONESIA: ANTARA PENGAKUAN KONSTITUSIONAL DAN IMPLEMENTASI DI PROVINSI PAPUA BARAT DAYA - Adirandi M Rajab; Moh. Ery Kusmiadi (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
From a constitutional perspective, the recognition of customary law embodies the principles of a democratic state governed by the rule of law that respects diversity. The state is obliged not only to normatively acknowledge the existence of customary law communities but also to guarantee their protection and uphold their constitutional rights. Such recognition must be realized through concrete policies, including the strengthening of customary institutions, the recognition of customary territories, the protection of customary land rights, and the inclusion of indigenous communities in all development processes affecting their lands and livelihoods. Furthermore, strengthening the enforcement of customary law in Southwest Papua is crucial, given the strategic role indigenous communities play in maintaining environmental balance and the sustainability of natural resources. The various forms of local wisdom found within indigenous communities have proven effective in preserving ecosystems and preventing the overexploitation of natural resources. Therefore, customary law should not be viewed as an obstacle to development, but rather as a strategic partner in achieving sustainable and equitable development.